Impact of Political Instability on Economic Growth in CEE Countries - Cela, Arjona; Hysa, Eglantina (Economy of Regions, 2021)
Political instability is often considered to have a negative influence on economic growth. Hence, the study aims to examine whether instability of the political environment (measured by the political stability index and duration of the chief executive in the office) significantly influences economic growth in Central and Eastern European (CEE) countries. The methodology used is a fixed effects model for panel data analysis where the dependent variable is the real growth of gross domestic product (GDP) per capita. The data covers the period from 2006 to 2016 for 13 CEE countries. Additionally, the study considered other macroeconomic variables, such as investment, inflation, human capital, trade openness, etc. The research findings indicate that the political stability index has a positive effect on economic growth, as expected and predicted in the literature. However, the indicator of the years the chief executive has been in the office has shown a negative effect. This effect appears to be weakly significant only for the second variable. These findings allowed us to conclude that the political stability index positively influences economic growth, while the years the chief executive stays in the office has a negative effect. Frequent changes in the cabinet can actually have a positive impact in transition countries characterised by corruption, meaning that the long stay of a chief executive in the office can lead to power abuse.